Warrants for signal coordination - Sophon Wathanaoran; Jones, John Hugh; Andreassend, David C.; Marler, Nicholas W.; Government of Thailand (Bangkok : Asian Institute of Technology, 1978)
This study is aimed at the determination of the conditions under which the coordination of signals are warranted. Robertson's platoon dispersion model was used in a simulation exercise to study the behaviour of a platoon movement between two intersections and through several intersections. The study was made by varying the general f actors of traffic flow, such as the discharge rates, cycle lengths, green splits, speeds, signal spacings, and offsets. These were fed into the computer as data. A simple relationship of flow, the average speed of vehicles in the platoon, and the distance to second intersection was found for the case of coordination of two intersections. The warrant for coordination of two intersections was, then, established from this relationship, and has the form of: The warrant flow = Kd , veh/h (through traffic) V where Kd = constant for a particular distance to the second intersection and for a specified acceptable percentage of flow passing the second intersection, veh-km/h2 V = average speed of vehicles in the platoon, km/h. For coordination of several intersections, each pair of intersections should satisfy the warrant for coordination of two intersections. A route in Bangkok was selected as an illustration. The present level of sophistication of equipment for signal coordination was studied.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Traffic signs and signals -- Thailand -- Bangkok; Traffic engineering -- Thailand -- Bangkok